"Liebe Schwester" 'Dear Sister': Luise Rinser's Unique Relationship with Her Readers - Julia Trumpold (Studies in 20th & 21st Century Literature, 2025)
The life of German author Luise Rinser (1911-2002) spanned almost an entire century. During this time, she witnessed and chronicled two world wars as well as many political and cultural changes in her novels, short stories, essays, and biographical writings. Rinser is a problematic figure as she has retrospectively cleansed and embellished her life story when writing her autobiographical texts. However, the focus of this article is Rinser’s unique relationship to her readers in her autobiographical writing. I argue readers perceived their relationship with the author as a friendship and, even if Rinser did not return that friendship directly, there is a reciprocity between this author and her readers that is rare in the literary world.
Keywords: Rinser; 20th Century Literature; Letters; Autobiography